Optimizing Burn Injury Care: A Comparative Network Meta-Analysis of Skin Grafts' Efficacy - Del Rosario Puling, Imke Maria; Pramana Giri, Nyoman Deva; Almadita, Teresa; Limantara, Jane; Arviansyah, Arviansyah (Fakultas Kedokteran Universitas Brawijaya, 2025)
Burn injuries, causing approximately 180,000 deaths. Skin grafting serves as a cornerstone intervention in burn injury management. This study aimed to evaluate the efficacy of different types of skin grafts in promoting the healing process of burn injuries. The outcomes of the study were the reepithelialization time and repigmentation rate of skin graft. Quality appraisal was done using ROBINS-I and the Newcastle Ottawa Scale, while network and single arm meta-analysis were conducted using R-Studio. A literature search across 6 databases resulted in the selection of 7 articles. Quality assessment categorized 6 studies as low- and 1 as moderate-risk of bias studies. The device facilitated autologous skin cell increase in reepithelialization rate (OR=5.21; 95% CI=0.24-114.41), followed by autologous skin cell and synthetic graft (OR=0.47; 95% CI=0.04-5.98), topical agent (OR=0.30; 95% CI=0.06-1.47), and Xenograft (OR=0.09; 95% CI=0.00-4.89). Furthermore, the single-arm meta-analysis showed an overall repigmentation rate of 61.49%, with xenograft displaying the highest repigmentation rate (87.50%), followed by synthetic graft (70.32%), and autologous skin cell (37.54%). Xenografts have proven effective in promoting burn wound healing. Nevertheless, the outstanding efficacy and minimal repigmentation of device-facilitated autologous skin cell transplantation highlight its potential in clinical practice.